Return on investment from fuel treatments to reduce severe wildfire and erosion in a watershed investment program in Colorado. (1st August 2017) - Jones, Kelly W.; Cannon, Jeffery B.; Saavedra, Freddy A.; Kampf, Stephanie K.; Addington, Robert N.; Cheng, Antony S.; MacDonald, Lee H.; Wilson, Codie; Wolk, Brett
Abstract: A small but growing number of watershed investment programs in the western United States focus on wildfire risk reduction to municipal water supplies. This paper used return on investment (ROI) analysis to quantify how the amounts and placement of fuel treatment interventions would reduce sediment loading to the Strontia Springs Reservoir in the Upper South Platte River watershed southwest of Denver, Colorado following an extreme fire event. We simulated various extents of fuel mitigation activities under two placement strategies: (a) a strategic treatment prioritization map and (b) accessibility. Potential fire behavior was modeled under each extent and scenario to determine the impact on fire severity, and this was used to estimate expected change in post-fire erosion due to treatments. We found a positive ROI after large storm events when fire mitigation treatments were placed in priority areas with diminishing marginal returns after treating >50–80% of the forested area. While our ROI results should not be used prescriptively they do show that, conditional on severe fire occurrence and precipitation, investments in the Upper South Platte could feasibly lead to positive financial returns based on the reduced costs of dredging sediment from the reservoir. While our analysis showed positive ROI focusing only on post-fire erosion mitigation, it is important to consider multiple benefits in future ROI calculations and increase monitoring and evaluation of these benefits of wildfire fuel reduction investments for different site conditions and climates. Highlights: We estimated potential return on investment from wildfire risk mitigation. Simulated fuel treatments were effective at reducing simulated post-fire erosion. Return on investment varied by placement of fuel treatment and extent treated. Return on investment varied with the size of simulated storms. Maximum financial return occurred with 50–80% of forested area treated.